Respuesta :
Answer:
[tex]f(-1)=5[/tex]
Step-by-step explanation:
We know that the equation is
[tex]f(x)=-4x^3+2x^2-1[/tex]
We can then plug -1 in for x
[tex]f(-1)=-4(-1)^3+2(-1)^2-1\\\\f(-1)=-4(-1)+2(1)-1\\\\f(-1)=4+2-1\\\\f(-1)=5[/tex]
ANSWER
[tex]f( - 1) = 5[/tex]
EXPLANATION
The given function is
[tex]f(x) = - 4 {x}^{3} + 2 {x}^{2} - 1[/tex]
We substitute x=-1 to obtain:
[tex]f( - 1) = - 4 {( - 1)}^{3} + 2 {( - 1)}^{2} - 1[/tex]
We simplify to obtain;
[tex]f( - 1) = 4 + 2 - 1[/tex]
.
This evaluates to
[tex]f( - 1) = 5[/tex]